Partycypacja w lokalnych wydarzeniach kulturalnych studentów pierwszego roku Wydziału Nauk Społecznych Uniwersytetu Zielonogorskiego = Participation in local cultural events by first-year students of the Faculty of Social Sciences, University of Zielona Gora - Pasterniak-Kobyłecka, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Participation in cultural activities plays an important role in the lives of young adults, influencing their interests and the development of their value systems. This study, conducted among 168 first-year students at the Faculty of Social Sciences, University of Zielona Gora, aimed to identify the cultural institutions most frequently visited by students during the winter term of the 2022/2023 academic year and to assess the challenges they faced in accessing these venues.
Keywords: kultura; instytucje kultury; wzory aktywności w kulturze; culture; cultural institutions; patterns of activity in culture